Performance analysis of lattice reduction‐assisted precoder for multi‐user millimeter wave MIMO system. (5th May 2021) - Kandar, Debdatta; Sur, Samarendra Nath; Singh, Arun Kumar; Nandi, Sukumar
Summary: Millimeter wave communication and massive MIMO technology are important ingredients for the future generation communication system. In this context, hybrid precoding (HP) is one of the most promising solutions, and it becomes utterly important in the case of the multi‐user scenario. In this paper, authors have analyzed the performance of the lattice reduction aided fully connected structured precoder for millimeter wave massive MIMO under multi‐user scenario. This paper deals with Korkine–Zolotareff (KZ) and Lenstra–Lenstra–Lovász (LLL) algorithms for the lattice reduction (LR). And the presented results show the performance comparison between zero forcing (ZF), minimum mean squared error (MMSE)‐based linear precoder with LLL algorithm‐based reduction‐based ZF (LLR‐ZF), LLR‐MMSE, KZ‐ZF, KZ‐MMSE, and Kalman filter‐based precoder. Here, the performance of the precoders has been evaluated based on spectral efficiency, energy efficiency diversity order, and bit error rate. This work conveys some important findings: (i) effectiveness of the lattice reduction aided precoder in multi‐user scenario; (ii) numerical results pointed out that at low SNR condition, KZ‐aided MMSE hybrid precoder provides 4‐dB performance than a Kalman filter‐based precoder; (iii) KZ‐MMSE hybrid precoder outperforms the other precoder. Abstract : This study demonstrates that the LR‐aided precoders (LLR‐ZF, KZ‐ZF, LLR‐MMSE, and KZ‐MMSE) perform much better than the conventional linear precoder in terms of BER, SE, and EE for a mMIMO system and also demonstrates that the LR‐aided MMSE precoder performs much better than Kalman‐based precoder in low SNR region.